Evaluation of Different Treatment Modalities for Rehabilitation of Mandibular Atrophy - Hanan Mahmoud¹*, Mohamed Magdale² (AlQalam Journal of Medical and Applied Sciences, 2020)
Long term edentulism may lead to residual alveolar bone resorption and consequently flat ridge. A flat ridge is associated with difficulties in providing successful prosthesis. Lack of adequate support, retention and denture stability are the most common problems. Successful restoration can be done with various conventional and contemporary treatment options. As each patient has his own specific clinical situation, treatment plans will be changed accordingly. In this study, three different treatment modalities were used to rehabilitate mandibular flat ridges, namely: implant supported overdenture, precision attachment supported partial dentures and a combination of precision attachment with implant supported bilateral distal extension removable partial denture. The three modalities were successful in terms of retention, function, esthetic and patient satisfaction.